Organized Crime and Illicit Trade How to Respond to This Strategic Challenge in Old and New Domains (Springer International Publishing, 2018)
"This title is a unique contribution, taking scholarship forward by developing new arguments around the development of organised crime. The latter makes the book particularly relevant, giving it great currency beyond a scholarly audience alone." Mark Shaw, Director of the Global Initiative against Transnational Organized Crime "This collection brings together a range of the most authoritative experts on organised crime, going beyond traditional responses and research to bridge the gap between academic and policy debates. Effective and comprehensive, the volume will be of great use to students, academics and practitioners." Sasha Jesperson, Director of the Centre for the Study of Modern Slavery at St Mary's University Twickenham, UK This book is a comprehensive integrated response to the challenges of transnational organised crime beyond traditional law-enforcement driven recommendations. Unlike much of the existing literature on organised crime, it is less focused on the problem per se as it is on understanding its implications. The latter, especially in fragile and conflict regions, amount to strategic challenges for the state. Whereas most commentators would agree that criminal activities are harmful, this volume addresses the questions of 'how?', 'for whom?' and, controversially, 'are they always harmful?' The volume is authored by experts with multi-year experience analysing criminal activities and doing so through lenses of conflict and security, development, and technology to engage academics, practitioners and policy makers. Virginia Comolli is Senior Fellow for Security and Development at The International Institute for Strategic Studies Vanda Felbab-Brown is a Senior Fellow at the Center for 21st Century Security and Intelligence, The Brookings Institution. Camino Kavanagh is an international consultant and Advisor to the UN Group of Governmental Experts on Cyber Security and ICT4 Peace Foundation. Karl Lallerstedt is Programme Director for Illicit Trade, Financial and Economic Crime at the Global Initiative against Transnational Organised Crime and co-founder of Black Market Watch. Tuesday Reitano is Deputy Director of the Global Initiative against Transnational Organised Crime and a Senior Research Associate at the Institute for Security Studies, Pretoria.